Framing The Responsibility of Public-Private Partnerships (PPPs) on Space Technology in International Law - Puspita, Natalia Yeti; Boydston, Natasha Gusti Wahyu Puspitasari (International Law Department, Faculty of Law Universitas Padjadjaran, 2023)
Public-Private Partnerships (PPPs) have gained popularity as a way to use resources and expertise from the private sector to support governmental space activities. In the event of a space-related incident, the division of duties and liabilities between public and private partners may be complicated. Clarifying the division of duties and liabilities between public and private actors is necessary given the rising participation of private companies in space activities.. With the growing involvement of private entities in space activities, there is a need to clarify the allocation of responsibilities and liabilities between public and private actors. Who is held responsible when a private company causes a technological disaster strike? On what basis can the responsibility be made, understood from international law? The research is normative legal research, where the data is collected through a statutory and case approach. The study results show that Public-private partnerships (PPPs) in outer space activities raise complex questions regarding responsibility. Responsibility refers to the Liability Convention on the Outer Space Treaty. The treaty emphasizes that states bear international responsibility for their national activities in outer space, including those conducted by private entities under their jurisdiction. However, the treaty does not explicitly address the specific responsibilities of private actors. Private companies only bear indirect international responsibility. PPPs need to consider the notion of shared responsibility, which acknowledges the contributions of both public and private actors and emphasizes cooperation and transparency